1992
DOI: 10.2105/ajph.82.10.1399
|View full text |Cite
|
Sign up to set email alerts
|

The search for meaning: RU 486 and the law of abortion.

Abstract: The advent of RU 486 (mifepristone), a steroid analogue capable of inducing menses within 8 to 10 weeks of a missed menstrual period, has provoked a firestorm of concern and controversy. When used in conjunction with prostaglandin (RU 486/PG), it is at least 95% effective. Used in France principally to terminate confirmed pregnancies very early in the process of gestation, RU 486 raises many interesting legal questions. This article focuses on whether and how RU 486/PG can be accommodated within the framework … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

1992
1992
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 14 publications
0
2
0
1
Order By: Relevance
“…The issue of medical abortion with RU 486 appeared in the American news media in July 1992 when Leona Benten, a pregnant California woman, attempted to bring RU 486 tablets (obtained in Great Britain) into the United States for her personal use. Because the Food and Drug Administration has not approved RU 486, importation of the drug is also banned (Banwell & Paxman, 1992). United States customs officials confiscated the drug from Benten, and this event fueled the American debate over the use of RU 486 in this country.…”
Section: History and Developmentmentioning
confidence: 99%
“…The issue of medical abortion with RU 486 appeared in the American news media in July 1992 when Leona Benten, a pregnant California woman, attempted to bring RU 486 tablets (obtained in Great Britain) into the United States for her personal use. Because the Food and Drug Administration has not approved RU 486, importation of the drug is also banned (Banwell & Paxman, 1992). United States customs officials confiscated the drug from Benten, and this event fueled the American debate over the use of RU 486 in this country.…”
Section: History and Developmentmentioning
confidence: 99%
“…The historian William McNeill suggested that the Spanish conquest of the Aztec empire was made possible by a devastating outbreak of smallpox, a new disease inadvertently introduced to the Aztecs by the Europeans.2 Alfred Crosby has pointed to a number of similar examples.3 While some of the specifics are still controversial, the archaeological evidence also favors the hypothesis that, in at least some regions of North America, European contact and introduced disease initiated a rapid decline in indigenous populations. 4 This spread of infectious diseases to new areas is thus a strong historical lesson. But even today history has a tendency to repeat.…”
Section: Global Microbial Traffic and The Interchange Of Diseasementioning
confidence: 99%
“…Etant donné que la plupart des femmes souhaitant interompre une grossesse préfèrent agir au plus vite et que les avortements précoces sont strs et faciles à réaliser, les interventions accomplies au counl des premières semaines sont d'un intérêt particulier. De plus, l'intemrption rapide de la grossesse contribue à éviter, dans une certaine mesure, la honte sociale, les jugements religieux et les sanctions pénales qui, actuellement, limitent ou empêchent I'accès des femmes à I'avortement dans le monde entier (Banwell, Paxman 1993).…”
unclassified